Sonographically Based Diagnosis of Contralateral Malignancy in Preoperative Patients With Papillary Thyroid Microcarcinoma. (1st May 2015) - Kim, Dong Wook; Park, Ha Kyoung; Ha, Tae Kwun; Kim, Sang Hyo; Jung, Soo Jin; Kim, Do Hun; Bae, Sang Kyun
Abstract : Objectives: We aimed to assess the usefulness of sonographically based diagnosis to predict whether contralaterally located dominant thyroid nodules are malignant or benign in patients with known papillary thyroid microcarcinoma. Methods: We studied 143 patients with primary papillary thyroid microcarcinoma who underwent preoperative thyroid sonography. Each dominant thyroid nodule was prospectively classified into 1 of 5 diagnostic categories by a single radiologist: benign, probably benign, borderline, possibly malignant, and malignant. We calculated the efficacy of sonographic diagnosis for contralateral malignancy by using histopathologic or long‐term sonographic follow‐up results as reference standards. Results: Of the 143 primary papillary thyroid microcarcinomas, 17 showed satellite carcinomas; hence, the bilaterality rate in all patients was 11.9% (17 of 143). Real‐time sonography of the contralateral thyroid yielded no thyroid nodules (n = 55) and benign (n = 52), probably benign (n = 10), borderline (n = 13), possibly malignant (n = 4), and malignant (n = 9) nodules. When the borderline sonographic class was excluded, the sensitivity, specificity, positive and negative predictive values, and accuracy of sonographic diagnosis for detecting contralateral malignancy were 86.7%, 100%, 100%, 98.3%, and 98.5%, respectively. Within individual sonographic classes for the dominant thyroid nodules, the diagnostic accuracy rates for classes IV and V (possibly malignant and malignant) were higher than those for other classes. Conclusions: Sonographically based diagnosis may be helpful for detection of contralateral malignancy in preoperative patients with papillary thyroid microcarcinoma.